Recent Advances and Challenges in Nanodelivery Systems for Antimicrobial Peptides (AMPs) - Ziyan Tang; Quantao Ma; Xiaoling Chen; Tianbao Chen; Yuan Ying; Xinping Xi; Lei Wang; Chengbang Ma; Chris Shaw; Mei Zhou (MDPI AG, 2021)
Antimicrobial peptides (AMPs) can be used as alternative therapeutic agents to traditional antibiotics. These peptides have abundant natural template sources and can be isolated from animals, plants, and microorganisms. They are amphiphilic and mostly net positively charged, and they have a broad-spectrum inhibitory effect on bacteria, fungi, and viruses. AMPs possess significant rapid killing effects and do not interact with specific receptors on bacterial surfaces. As a result, drug resistance is rarely observed with treatments. AMPs, however, have some operational problems, such as a susceptibility to enzymatic (protease) degradation, toxicity in vivo, and unclear pharmacokinetics. However, nanodelivery systems loaded with AMPs provide a safe mechanism of packaging such peptides before they exert their antimicrobial actions, facilitate targeted delivery to the sites of infection, and control the release rate of peptides and reduce their toxic side effects. However, nanodelivery systems using AMPs are at an early stage of development and are still in the laboratory phase of development. There are also some challenges in incorporating AMPs into nanodelivery systems. Herein, an insight into the nanotechnology challenges in delivering AMPs, current advances, and remaining technological challenges are discussed in depth.